The concept of "the love of wisdom" in Proverbs (8) : a comparative-philosophical clarification - Gericke, Jaco (Journal for semitics, 2013)
The word "philosophy" can be literally rendered "the love of wisdom". However, while etymological definitions are not always reliable as to the actual use of words, in some sense it is not an inaccurate notion of what some of the ancient Greek philosophers thought they were up to. The ancient Greek senses of "love" and "wisdom" were, however, not univocal. In addition, though the Hebrew Bible is not as a rule considered philosophy proper in terms of genre, the Book of Proverbs does contain several verbal references to the love of wisdom. In this paper the author seeks to elucidate and compare what the love of wisdom meant in both the Greek and Hebrew contexts and how they might have conceptually overlapped and diverged.